The Effect of Guided Discovery Model with LKS of Mind Mapping on Learning Outcomes and Learning Activities in Physics Learning at SMA 1 Cluring - Mia Eka Lestari; Subiki Subiki; Albertus Djoko Lesmono (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
This article reported the results of an experimental research about the effect of guided discovery with LKS mind mapping the results of teaching and learning of physics activities learning in SMAN 1 Cluring. The objectives of this research were to describe the learning activities during guided discovery with LKS mind mapping. Thie guided discovery’s model with LKS mind mapping measured the cognitive learning outcomes. The data of the cognitive learning outcomes in elasticity was collected by using post test. Then, the data collected was analyzed by using independent sample t-test (SPSS 22). The difference of the achievement between experiment class and control class was did by obtained significant value of 0.759 and 0.895 It means the result of this research proved that the use of guided discovery model with LKS mind mapping significantly affected the cognitive learning outcomes at eleventh grade SMAN 1 Cluring. The design of this research was post test only control group design. The data of the learning activities was collected by using observation. Based on the data, the average of the learning activities was 85,76% which means active.